Acanthomatous ameloblastoma: A rare presentation - Ramaswamy Pachigolla; Raga Geethika Velugubantla; Sai Kiran Chennoju; Swathi Erva (Wolters Kluwer Medknow Publications, 2016)
Ameloblastoma is the most frequent odontogenic tumor arising from dental epithelium. It is characterized by its histological resemblance to the enamel organ of the developing tooth germ; but enamel formation is not observed. Acanthomatous ameloblastoma is considered an aggressive odontogenic tumor characterized by irregular verrucous masses adjacent to the tooth, consisting of sheets of keratinizing odontogenic epithelium. Here we are reporting a case of 35-year-old male with swelling on left body of the mandible region which was diagnosed as acanthomatous ameloblastoma based on clinical, radiographic and histopathological features.